How to build a lichen: from metabolite release to symbiotic interplay. Issue 4 (4th March 2023) - Pichler, Gregor; Muggia, Lucia; Carniel, Fabio Candotto; Grube, Martin; Kranner, Ilse
Summary: Exposing their vegetative bodies to the light, lichens are outstanding amongst other fungal symbioses. Not requiring a pre‐established host, 'lichenized fungi' build an entirely new structure together with microbial photosynthetic partners that neither can form alone. The signals involved in the transition of a fungus and a compatible photosynthetic partner from a free‐living to a symbiotic state culminating in thallus formation, termed 'lichenization', and in the maintenance of the symbiosis, are poorly understood. Here, we synthesise the puzzle pieces of the scarce knowledge available into an updated concept of signalling involved in lichenization, comprising five main stages: (1) the 'pre‐contact stage', (2) the 'contact stage', (3) 'envelopment' of algal cells by the fungus, (4) their 'incorporation' into a pre‐thallus and (5) 'differentiation' into a complex thallus. Considering the involvement of extracellularly released metabolites in each phase, we propose that compounds such as fungal lectins and algal cyclic peptides elicit early contact between the symbionts‐to‐be, whereas phytohormone signalling, antioxidant protection and carbon exchange through sugars and sugar alcohols are of continued importance throughout all stages. In the fully formed lichen thallus, secondary lichen metabolites and mineral nutrition are suggested to stabilize the functionalities of the thallus, including the associated microbiota.